Comparative analysis of the Traditional, Reverse and European Centre for Disease Prevention and Control algorithms and utilization of WHO NET software for syphilis serodiagnosis in a tertiary care hospital in Chengalpet, South India - Abirami Lakshmy Jayachandran; Sankara Dhanapaul; Visuvasam Joshua; Balan Kandasamy (Journal of Krishna Institute of Medical Sciences University)
Background: Syphilis is a Sexually Transmitted Disease (STD) caused by Treponema pallidum with significant public health importance. Based on the clinical presentation syphilis is classified into primary, secondary, tertiary and latent syphilis. Lab diagnosis of syphilis can be done by serological methods using specific treponemal and non treponemal tests. Testing strategies like traditional, reverse and European Centre for Disease Prevention and Control (ECDC) are currently used as principal diagnostic algorithms. Aim and Objectives: To compare the seropositivity among three diagnostic algorithms for syphilis serodiagnosis and data analysis using WHO NET software. Material and Methods: All the samples received for syphilis serology were tested by Rapid Plasma Reagin (RPR) and rapid immunochromatographic card methods. Three diagnostic algorithms were used. In traditional algorithm, the sample was first tested with RPR (non-treponemal test) and if reactive then interpreted as a case of syphilis. In reverse algorithm, a specific treponemal card test was done and if reactive a second non treponemal test like RPR was performed. A second rapid immunochromatographic test was also performed. In the case of the ECDC algorithm two specific card tests were performed and interpreted. WHO NET software was utilized for data entry and analysis. The coefficient of agreement (k value) was analyzed by using QuickCalcs GraphPad software. Results: A total of 1292 samples were tested, and 4 (0.3%) samples were reactive by traditional algorithm. By reverse and ECDC algorithm 14 (1.08%) of the samples were considered as reactive. Overall, four samples were identified as cases of definite/current syphilis and ten samples were considered as cases of probable early current / latent or treated syphilis. Reverse algorithm and ECDC algorithm detected more cases. The missed diagnosis percentage was 10 (71.42%) for traditional algorithm. Antenatal patients comprised of 334 (25.85%) samples with seropositivity of 0.29%. Maximum samples were received from the age group of 21 to 30 years 484 (37.46%). Strong degree of agreement was observed between reverse and ECDC algorithm (k value- 0.832). Conclusion: Reverse or ECDC algorithm can be implemented in the laboratory routinely to avoid missing cases of early syphilis. The specific treponemal card tests available in immunochromatography formats are easy to perform and interpret. The usage of WHO NET for analysis of data and along with including specific comments individualized for each patient in the lab reports could give valuable insight.